CYBERFEMINISM: PHILOSOPHICAL REFLECTION ON GENDER, TECHNOLOGY, AND DIGITAL SUBJECTIVITY. - KHVOINYTSKA-PEREIMA, KHRYSTYNA (Humanities Studies, 2025)
Cyberfeminism, emerging in the late 20th century, represents a critical theoretical and practical engagement with the intersections of gender and digital technology. It challenges both patriarchal structures embedded in technological development and the philosophical assumptions underlying human -- machine relations. This article explores cyberfeminism as a philosophical discourse, examining its epistemological, ontological, and political dimensions. Special attention is given to the tension between essentialist and posthumanist interpretations of cyberfeminism, as well as its implications for digital subjectivity, embodiment, and power relations in cyberspace. Cyberfeminism represents a critical intersection of feminist philosophy, technology, and digital culture, offering new ways of theorizing identity, embodiment, and power in the information age. This article examines the philosophical foundations of cyberfeminism, tracing its emergence from postmodern feminist thought and its engagement with questions of technoscience, subjectivity, and the politics of cyberspace. Particular attention is given to the ways cyberfeminist theory challenges essentialist notions of gender, destabilizes traditional dualisms between human and machine, and reimagines the possibilities of agency in virtual environments. By analyzing the contributions of thinkers such as Donna Haraway and later developments in third-wave feminist discourse, the paper explores how cyberfeminism not only critiques the gendered structures of technological production but also envisions emancipatory potentials within digital culture. Ultimately, the study argues that cyberfeminism constitutes a transformative philosophical framework for understanding the entanglement of gender and technology in contemporary society. The research objectives: explore the ideas and basic foundation of cyberfeminist ideas. Make an attempt to penetrate into the hidden foundations of these ideas. Also, make an attempt at a comparative analysis of a number of feminist and philosophical teachings. Research methodology. Teaching the ideas of feminism and cyberfeminism is complex and multifaceted. A comprehensive, systematic approach is required to analyze this topic. Therefore, a number of methods were used in this study: induction, deduction, historicism and the systemic method. Connection with previous studies. The problem of cyberfeminism is of interest to a large number of scientists. We find research data in the scientific works of such scientists as: Shoshana Zuboff, Mary Flanagan, Austin Booth, Marie Hicks and many other researchers. However, this topic remains an inexhaustible source of versatility for new philosophical research.